THE EFFECT OF SOCIAL MEDIA MARKETING ON BRAND EQUITY AND CONSUMER RESPONSE IN LUXURY FASHION BRAND - Miracle Bernadus; Paulus Kindangen; Maria V. J. Tielung (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
This study aims to analyze and determine the effect of social media marketing on brand equity and consumer response in luxury fashion brands, especially in Manado, Indonesia. The data analysis method used Structural Equation Modeling - Partial Least Square (SEM-PLS) in this study. This study used a questionnaire to collect data from luxury fashion brand users by distributing it to female consumers of luxury fashion brands in Manado. The findings suggest the test results that have been conducted that social media marketing has a positive and significant effect on the brand equity of luxury brands. The test results show that brand equity affects consumer responses as measured by brand preference, consumer willingness to pay premium prices, brand loyalty, and commitment to maintaining a relationship with a brand, especially luxury fashion brands.   Keywords: social media marketing, brand equity, consumer response